Cementitious Spray Dryer Ash-Tire Fiber Material for Maximizing Waste Diversion - Charles E. Riley; Rebecca A. Atadero; John W. van de Lindt; Paul R. Heyliger (Advances in Civil Engineering)
Spray dryer absorber (SDA) material, also known as spray dryer ash, is a byproduct of coal combustion and flue gas scrubbing processes that has self-cementing properties similar to those of class C fly ash. SDA material does not usually meet the existing standards for use as a pozzolan in Portland cement concrete due to its characteristically high sulfur content, and thus unlike fly ash, it is rarely put to beneficial use. This paper presents the results of a study with the objective of developing beneficial uses for SDA material in building materials when combined with tire fiber reinforcement originating from a recycling process. Specifically, spray dryer ash was investigated for use as the primary or even the sole binding component in a mortar or concrete. This study differs from previous research in that it focuses on very high contents of spray dryer ash (80 to 100 percent) in a hardened product. The overarching objective is to divert products that are normally sent to landfills and provide benefit to society in beneficial applications.